Alternativas de mitigação da compactação do solo para implantação da soja em áreas de terras baixas no Rio Grande do Sul - Donato, Gabriel (2022)
The state of Rio Grande do Sul is the largest national producer of irrigated rice. However, problems with resistance of weeds to herbicides used for this crop have made its use unfeasible in some areas. Crop rotation with soybeans has been an alternative on the rise in recent harvests. However, in view of the characteristics of this environment, such as poor drainage, low hydraulic conductivity and the presence of a compacted layer close to the soil surface, they have provided frequent alternations between periods of deficit in terms of water excess, compromising establishment, root growth, nodulation, growth of plants and soybean productivity. In this context, a two-year study was carried out in lowland areas, in the 2019/20 and 2020/21 harvests, with alternatives that provide a crop with lower risks. The results generated three articles. The first article aimed to evaluate the benefits in soil physical attributes, as well as in the growth and productivity of soybean grains as a function of soil management carried out in the off-season and the use of mechanisms associated with the seeder-fertilizer for two cultivars of soybeans, and in five locations in the state of RS, in one or two harvests. For this, the experiment was conducted in Santa Maria, Candelária and Dom Pedrito in the 2019/20 and 2020/21 harvests, and in Pelotas and Jaguarão in the 2019/20 harvest. Factor A levels were composed of soil management and seeder mechanism: (A1) seeding without soil preparation (SWSP) + double disc (DD) in the seeder; (A2) SWSP+ chisel (CH) on the seeder; (A3) disc harrow+DD; (A4) scarified+DD. Factor D levels were composed of two soybean cultivars: (D1) NS 6601 and (D2) BMX Valente. The second study aimed to determine the benefits of mechanical soil management in reducing physical impediments and the effects on morphophysiological parameters and soybean productivity, in addition to quantifying the energy demand of the tractor for operations. The study was conducted in the city of Santa Maria-RS in the 2019/20 and 2020/21 harvests. Factor A levels were: (A1) seeding without soil preparation (SWSP) + double disc (DD) in the seeder; (A2) SWSP+turbo helical disc (HD) on the seeder; (A3) SWSP+ chisel (CH) on the seeder; (A4) disc harrow+DD; (A5) scarified+DD and (A6) chisel tillage+DD. Factor D levels were composed of two soybean cultivars: (D1) NS 6601 and (D2) BMX Valente. Based on the main results, scarification reduces soil density and increases macroporosity up to 0.3 m depth, allowing better initial plant establishment, greater root growth and greater grain yield. Of the mechanisms associated with the seeder, the HS promotes the greatest root growth and grain yield. Sowings with DD and DT present greater operational capacity and lower fuel consumption, however, they do not attenuate the damage caused by soil compaction, resulting in lower soybean productivity.